Phellinocis, a new genus of Neotropical Ciidae (Coleoptera: Tenebrionoidea) - Lopes-Andrade, Cristiano; Lawrence, John F. (Zootaxa, 2005)
Phellinocis gen. n. is described based on three species: P. romualdoi sp. n. (type species) from Brazil, P. erwini sp. n. from Panama and P. thayerae sp. n. from Costa Rica and Panama. Diagnostic characters of the genus include the oblong, highly convex, subglabrous body, strongly declined, convex to slightly concave and often fluted elytral apices, 8or 9-segmented antennae, short and concave prosternum, laminate prosternal process, and protibia with simple outer edge and two stout teeth at apex. Phellinocis romualdoi has two features not found in any other described species of Ciidae: intraspecific variation in antennal segmentation and presence of a setal patch on the first ventrite of the female. Comparisons are made with a number of other ciid genera, and the genus is placed in the tribe Ciini. A key to species of Phellinocis is provided, together with descriptions of external morphology of adults, and morphology of male genitalia.